Analisis Balik Kestabilan Lereng Bekas Disposal Area Dengan Menggunakan Metode Bishop di Tambang PT. Nusa Alam Lestari di Desa Salak, Kecamatan Talawi, Kota Sawahlunto, Provinsi Sumatera Barat. - Syakinah Hasibuan; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. Nusa Alam Lestari is a coal mine located in Salak village, Talawi sub-district, Sawahlunto city, West Sumatra Province. In 2006-2011, the mining system used was open pit mining, but at the end of 2011 mining continued with the underground mining system. Former mine open disposal used to be on the upper side of tunnel C2 which affected production from underground mines, is former disposal area slope condition (section A – A’) unstable so that landslides occurred in December 2019 of soil and rock has weakened material are identified in tht form of an avalanche arc. Slope geometry after landslide were slope height (H) = 35,7 meter, dip (α) = 70o, and bench width (L) = 13 meter.The method used in this research are the bishop method and hoek and bray method. The results from this research can conclued another thing follows. Data from laboratory tests were unit weight (γdry) = 18,06 kN/m3, unit weight (γsat) = 19,99 kN/m3, Cohession (C) = 18 kN/m2, and phi (φ) = 34o. And result from back analysis in landslide were (C) = 16 kN/m2, (φ) = 30o, (γ) = 14 kN/m3. Safety factor value before landslide used material properties from test laboratory in dry condition FK = 0,702 and in saturated condition FK = 0,676, whereas base on back analysis in dry condition FK = 0,667 and in the wet condition FK = 0,607. Slope geometri reccomendation by simplified bishop and safety factor value got are overall slope in the dry condition, H = 35,7 meter, L =13 meter, α = 55o with FK = 1,382, and in the saturated condition FK = 1,331. On single slope in the dry condition (H) = 17 meter, L = 13 meter, α = 45o so FK = 1,432, whereas in the saturated condition (H) = 13,5 meter and α = 40oso FK = 1,380. Reccomendation slope geometry (single slope) used hoek and bray method are in the dry condition (H) = 17 meter, L = 13 meter, α = 45o nilai FK = 1,46 and in the saturated condition (H) = 13,5 meter, L = 13 meter, α = 40o so FK = 1,33.Keywords: Disposal Area, Slope Stability, Bishop Method, Safety Factors, Back Analysis